Rotary motions of autonomous systems with pulse influence - Ali, N. A.; Yanchuk, S. V. (Ukrains’kyi Matematychnyi Zhurnal, 1997)
We study rotary motions for an autonomous second-order differential equation with pulse influence and periodic right-hand side and indicate some important properties of these motions. By using the numerical-analytic method, we establish sufficient conditions for the existence of rotary motions.